Plxnd1 Expression in Thymocytes Regulates Their Intrathymic Migration While That in Thymic Endothelium Impacts Medullary Topology - Choi, Young I.; Duke-Cohan, Jonathan S.; Tan, Jing; Gui, Jingang; Singh, Manvendra K.; Epstein, Jonathan A.; Reinherz, Ellis L. (Frontiers in Immunology, 2013)
An important role for plexinD1 in thymic development is inferred from studies of germline Plxnd1 knockout (KO) mice where mislocalized CD69+ thymocytes as well as ectopic thymic subcapsular medullary structures were observed. Given embryonic lethality of the Plxnd1-/- genotype, fetal liver transplantation was employed in these prior analyses. Such embryonic hematopoietic reconstitution may have transferred Plxnd1 KO endothelial and/or epithelial stem cells in addition to Plxnd1 KO lymphoid progenitors, thereby contributing to that phenotype. Here we use Plxnd1flox/flox mice crossed to pLck-Cre, pKeratin14-Cre or pTek-Cre transgenic animals to create cell-type specific conditional knockout (CKO) lines involving thymocytes (D1ThyCKO), thymic epithelium (D1EpCKO) and thymic endothelium (D1EnCKO), respectively. These CKOs allowed us to directly assess the role of plexinD1 in each lineage. Loss of plexinD1 expression on double positive (DP) thymocytes leads to their aberrant migration and cortical retention after TCR-mediated positive selection. In contrast, ectopic medulla formation is a consequence of loss of plexinD1 expression on endothelial cells, in turn linked to dysregulation of thymic angiogenesis. D1EpCKO thymi manifest neither abnormality. Collectively, our findings underscore the non-redundant roles for plexinD1 on thymocytes and endothelium, including the dynamic nature of medulla formation resulting from crosstalk between these thymic cellular components.